2014
DOI: 10.3324/haematol.2014.111112
|View full text |Cite
|
Sign up to set email alerts
|

A new prognostic score for AIDS-related lymphomas in the rituximab-era

Abstract: Methods Patients and data collectionWe performed a systematic review of the literature to identify prospectively conducted clinical trials that assessed therapeutic interventions for HIV-associated NHL. A detailed description of the search strategy has been previously reported 12 and is available in the Online Supplementary Appendix. We limited our dataset to only patients treated with rituximab-containing chemoimmunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 31 publications
3
40
0
2
Order By: Relevance
“…Despite an initial good response, the patient did not tolerate the treatment of the recurrent disease. The lower CD4 count during the treatment of the recurrent disease supports the current recommendation that the caveat underlying the efficacy and safety of rituximab is the CD4 count [27,[36][37][38].…”
Section: • Dual Expression But Not Dual Rearrangements Of Myc and Bcl2supporting
confidence: 61%
See 1 more Smart Citation
“…Despite an initial good response, the patient did not tolerate the treatment of the recurrent disease. The lower CD4 count during the treatment of the recurrent disease supports the current recommendation that the caveat underlying the efficacy and safety of rituximab is the CD4 count [27,[36][37][38].…”
Section: • Dual Expression But Not Dual Rearrangements Of Myc and Bcl2supporting
confidence: 61%
“…The use of rituximab in HIV-infected patients with NHLs has been debated, because of the associated increased risk of infectious deaths, a consequence of rituximab-induced B-cell depletion on a background of severe T-cell depletion [27,36]. Recent studies have highlighted the safety and efficacy of chemotherapy in combination with rituximab in patients with CD4 counts above 50 cells/µL [27,36,37]. The index patient had chemotherapy and rituximab following initial diagnosis and recurrence.…”
Section: • Dual Expression But Not Dual Rearrangements Of Myc and Bcl2mentioning
confidence: 99%
“…Various prognostic parameters have been used for predicting the treatment outcome of NHL [7, 11, 24]. Among them, the IPI is probably the most commonly used one [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the IPI is probably the most commonly used one [25]. Based on IPI, various systems such as FLIPI were designed for some special subtypes of lymphoma [24]. In this study, we have examined the efficacy of IPI parameters in HIV associated NHL (mostly BL and DLBCL).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports [9,10] have shown that other scores such as the HIV-score, the age-adjusted International Prognostic Index for non-Hodgkin Lymphoma and in a more comprehensive way, the AIDS-related lymphoma International Prognostic Index correlate with prognosis in HIV-infected patients with lymphoma treated with frontline rituximab-containing chemoimmunotherapy. However, in our experience, in the context of salvage therapy, these prognostic scores fail to identify the proportion of patients with a better prognosis, whereas only the evaluation of disease chemosensitivity and co-morbidities weight has a role.…”
mentioning
confidence: 99%